2013
DOI: 10.1371/journal.pone.0062283
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Programmed Ribosomal Frameshifting by Co-Translational Refolding RNA Hairpins

Abstract: RNA structures are unwound for decoding. In the process, they can pause the elongating ribosome for regulation. An example is the stimulation of -1 programmed ribosomal frameshifting, leading to 3′ direction slippage of the reading-frame during elongation, by specific pseudoknot stimulators downstream of the frameshifting site. By investigating a recently identified regulatory element upstream of the SARS coronavirus (SARS-CoV) −1 frameshifting site, it is shown that a minimal functional element with hairpin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 31 publications
1
54
1
Order By: Relevance
“…Deletion of SLA enhanced frameshifting to 72% of WT in the RSE background ( Figure 9C; RSE versus RSE+ SLA*), strongly suggesting that a hairpin upstream of the slippery site suppresses downstream frameshifting when an RSE is not present (or not formed). A previous study also revealed a suppressive role for a hairpin located 4-nt upstream of the slippery site in SARS-CoV, and this hairpin was able to suppress frameshifting stimulated by pseudoknots from a number of different viruses (31,64). The level of attenuation reported was sensitive to the stability of the stem as well as the distance from the slippery site (64).…”
Section: Possible Role For the Phylogenetically Conserved Sla Hairpinmentioning
confidence: 81%
See 1 more Smart Citation
“…Deletion of SLA enhanced frameshifting to 72% of WT in the RSE background ( Figure 9C; RSE versus RSE+ SLA*), strongly suggesting that a hairpin upstream of the slippery site suppresses downstream frameshifting when an RSE is not present (or not formed). A previous study also revealed a suppressive role for a hairpin located 4-nt upstream of the slippery site in SARS-CoV, and this hairpin was able to suppress frameshifting stimulated by pseudoknots from a number of different viruses (31,64). The level of attenuation reported was sensitive to the stability of the stem as well as the distance from the slippery site (64).…”
Section: Possible Role For the Phylogenetically Conserved Sla Hairpinmentioning
confidence: 81%
“…A previous study also revealed a suppressive role for a hairpin located 4-nt upstream of the slippery site in SARS-CoV, and this hairpin was able to suppress frameshifting stimulated by pseudoknots from a number of different viruses (31,64). The level of attenuation reported was sensitive to the stability of the stem as well as the distance from the slippery site (64). In PEMV, the basal portion of the SLA stem would be melted when a ribosome is positioned at the slippery sequence, but the remainder of the hairpin may provide mechanical resistance for 5 movement of the ribosome, thus suppressing frameshifting.…”
Section: Possible Role For the Phylogenetically Conserved Sla Hairpinmentioning
confidence: 86%
“…(C) Proposed basal SLA structure for SARS-CoV. The upstream SLA hairpin serves as a repressor of PRF (33)(34)(35). Sequences shown in blue are capable of pairing.…”
Section: Conserved Features Of Tombusvirid Rsesmentioning
confidence: 99%
“…Since internal H-type pseudoknots have not been reported in RSEs from any of these plant viruses, it has been proposed that these long-distance RNA bridges form an atypical pseudoknot that functionally replaces the internal pseudoknot that is common in animal virus RSEs (2,28,32). In addition, hairpins or artificial duplexes just upstream of the recoding site repress frameshifting in coronaviruses and PEMV2 (21,(33)(34)(35). Strikingly, in the absence of the upstream hairpin, the PEMV2 RSE is no longer required to stimulate frameshifting from the slippery site, suggesting that upstream hairpins may play significant roles in suppressing Ϫ1PRF.…”
mentioning
confidence: 99%
“…Conversely, the upstream hairpin in barley yellow dwarf virus (genus Luteovirus, family Luteoviridae, but related to tombusvirids) (43) was found to enhance frameshifting (18). In a third example, severe acute respiratory syndrome coronavirus, the upstream hairpin downregulated frameshifting activity (10). Thus, the effects of such RNA structures on frameshifting can vary significantly.…”
Section: Structural Features Of the Upper Portion Of The Rtsl Moderatmentioning
confidence: 99%